A Novel Benzofuran Derivative Moracin N Induces Autophagy and Apoptosis Through ROS Generation in Lung Cancer - Gao, Chengcheng; Sun, Xin; Wu, Zhipan; Yuan, Huahua; Han, Haote; Huang, Hongliang; Shu, Yuhan; Xu, Mengting; Gao, Ruilan; Li, Shouxin; Zhang, Jianbin; Tian, Jingkui (Frontiers in Pharmacology, 2020)
Introduction The leaves of Morus alba L is a traditional Chinese medicine widely applied in lung diseases. Moracin N (MAN), a secondary metabolite extracted form the leaves of Morus alba L, is a potent anticancer agent. But its molecular mechanism remains unveiled. Objective In this study, we aimed to examine the effect of MAN on human lung cancer and reveal the underlying molecular mechanism. Methods MTT assay was conducted to measure cell viability. Annexin V-FITC/PI staining was used to detect cell apoptosis. Confocal microscope was performed to determine the formation of autophagosomes and autolysosomes. Flow cytometry was performed to quantify cell death. Western blotting was used to determine the related-signaling pathway. Results In the present study, we demonstrated for the first time that MAN inhibitd cell proliferation and induced cell apoptosis in human non-small-cell lung carcinoma (NSCLC) cells. We found that MAN treatment dysregulated mitochondrial function and led to mitochondrial apoptosis in A549 and PC9 cells. Meanwhile, MAN enhanced autophagy flux by the increase of autophagosome formation, the fusion of autophagsomes and lysosomes and lysosomal function. Moreover, mTOR signaling pathway, a classical pathway regualting autophagy, was inhibited by MAN in a time- and dose-dependent mannner, resulting in autophagy induction. Interestingly, autophagy inhibition by CQ or Atg5 knockdown attenuated cell apoptosis by MAN, indicating that autophagy serves as cell death. Furthermore, autophagy-mediated cell death by MAN can be blocked by reactive oxygen species (ROS) scavenger NAC, indicating that ROS accumulation is the inducing factor of apoptosis and autophagy. In summary, we revealed the molecular mechanism of MAN against lung cancer through apoptosis and autophagy, suggesting that MAN might be a novel therapeutic agent for NSCLC treatment.